A Multidimensional Welfare Status of Leprosy Patients Living in a Suburban Area - Irawati, Yunia; Menaldi, Sri Linuwih SW; Harini, Melinda; Wahyuni, Luh Karunia; Alwin, Wanarani; Dwiranti, Astari; Menaldi, Adhityawarman; Luzanil, Sonny Tirta; Matsurah, Qaishum; ., Dadun; Kurniawan, Rico; Ruwaida, Ida; Wicaksono, Gunawan; Sahid, Muhammad Hidayat; Rahmayanti, Febrina; Priscilia, Florentina; Fitriana, Anis; Rahayu, Tri; Susiyanti, Made; Andayani, Gitalisa; Bani, Anna Puspitasari; Daniel, Hisar; Lestari, Yeni Dwi (UI Scholars Hub, 2021)
Leprosy has a high incidence of physical complications that will impact directly the physiological, economic, and social status of patients. Indonesia has a high burden of the disease, and several leprosy settlements are still spread in the country. Neglasari Village, Sitanala, Tangerang serves as one of the places of residence of people who have had leprosy. A health service initiative known as Identifikasi Tanda-Tanda Mata, Ekstremitas, dan Kulit pada Kusta (KATAMATAKU) was launched as a collaboration of health services among multi-departments (ophthalmology, dermatovenereology, and medical rehabilitation). Sitanala has a relatively high incidence of people who have had leprosy with disabilities of the hand, foot, and eye. As a continuation of this health service and combined with the efforts to improve the welfare of leprosy patients, in November 2019, a multidisciplinary program titled KATAMATAKU Universitas Indonesia, was conducted. This program aimed to determine the demographic data regarding the health, psychological, social, and economic status of the leprosy population at Sitanala The project consisted of a collaborative anti-stigma program by the Faculty of Psychology, Public Health, Social and Political Sciences, Cultural Sciences, Administrative Sciences, and Vocational Educational Program; thematic health program, which supports the improvement of physical abilities and empowerment of former leprosy patients, by the Faculty of Medicine, Dentistry, Nursing, and Pharmacy; thematic economics program, which aims to increase the economic capacity of the leprosy community, by the Faculty of Economics and Business, Mathematics and Natural Sciences, and Engineering. This program enabled the construction of a multidimensional management model, in which every aspect plays important roles to improve the patients’ quality of life.